PENGARUH STRUKTUR KEPEMILIKAN, KOMPLEKSITAS, DAN UKURAN PERUSAHAAN TERHADAP AUDIT FEE - Ahmad Sulaiman (2020)
The research has the objective to find out the influence of ownership structure, complexity, and size of company on the audit fee. Sample amounted to 95 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016, 2017 andi 2018 periods that were selected by purposive sampling. Multiple linear regression analysis is an analytical technique used for this study using SPSS Version 25 software. The significance level used is 5%. The results of testing obtained that (1) Ownership structure has a significant influence on the audit fee, (2) Complexity has a significant influence on the audit fee, and (3) Size of company has a significant influence on the audit fee.